TINGKAT PEMAHAMAN STANDAR PROSES KURIKULUM 2013 PADA GURU PPKN DALAM PROSES BELAJAR MENGAJAR DI SLTA SEDERAJAT SE-KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - Mery Fitria; Gimin '; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background lavel of this research is the level understanding the standars process curriculum 2013 in teaching and learning in PPKn. Curriculum 2013 has a standard process contained in Permendikbud N0. 65 Tahun 2013. In the education curriculum has important role in a process of learning, curriculum is provided as a lesson plan for students. Therefore the students do learning activities, in other to relive the competen generation, active, innovative, and personally responsible. Incosten curriculum along in the development of era makes the teachers have to understand the standars process in teaching and learning process curriculum also determine the type and quality of knowladge. always understand the standards process in the learning process and also determine the type and quality of curriculum knowledge. Therefore the writer write a topic “The level of the PPKn teacher’ understanding of curriculum 2013 standars process teaching and learning process at SLTA in Ujung Batu District Rokan Hulu”. Population of this research is all of SLTA in Ujung Batu the are 7 SLTA in Ujung Batu and the number of the simple is 14 PPKn teachers. To conduct this research the writer uses a questionnare hich is 28 questions and interview whichis 9 questions. This research uses qualitative data through percentage. The understand answere is about 68,20% the range is between 50,01%-75,00% it means “Good”. Based on the research finding it can be concluded that teachers have understood the standars process in curriculum 2013.Keywords: The lavel of understand, standar process in curriculum 2013